Peningkatan Kompetensi Siswa Kelas XII TITL 1 Keahlian Teknik Instalasi Tenaga Listrik Smk Negeri 2 Depok pada Mata Pelajaran Sistem Pengendali Elektronik Melalui Metode Kooperatif STAD Tahun Pelajaran 2018/2019 - Ruslan Ruslan (Transformasi Manageria: Journal of Islamic Education Management, 2022)
This study aims to determine the effectiveness of the Student Team Achievement Division (STAD) cooperative learning method with the help of Electronic Control System learning media in improving the competence of class XII students in Electrical Power Installation Engineering skills at SMKN 2 Depok in the subject of electronic control systems. This research is a classroom action research conducted in two cycles, with three meetings for each cycle. Each cycle in this study consisted of four stages of implementation, namely planning, implementing actions, observing, and reflecting. Data was collected using affective observation sheets, psychomotor observation sheets, and pre-test and post-test instruments. The instrument of affective observation sheet is used to determine students' competence in the affective aspect. The psychomotor observation sheet instrument was used to determine student competence in psychomotor aspects. Pre-test and post-test instruments were used to determine students' competence in cognitive aspects. The data analysis technique used is data reduction, data exposure, and conclusion drawing. The results showed an increase in student competence in the affective, psychomotor, and cognitive aspects after the implementation of the STAD technique cooperative learning method with the help of Electronic Control System learning media. In the affective aspect, there was an increase of 48.21%, with the percentage of students' affective aspects at the first meeting of 56%, increasing to 83% at the sixth meeting. In the psychomotor aspect there was an increase of 22.15%, with the average psychomotor score of students on job sheet 1 of 67.66, increasing to 82.65 on job sheet 4. In the cognitive aspect there was an increase of 110.9%, with a score of the average pre-test cycle 1 was 38.53, increased to 81.26 in the post-test cycle 2.Keywords: student competence, student team achievement division, electronic control system